A Method for Selecting Enterprise's Logistics Operation Mode Based on Ballou Model. (2nd July 2019) - Li, Feng; Fan, Zhi-Ping; Cao, Bing-Bing; Wang, Ze
Abstract : The right choice of logistics operation mode is not only the foundation for improving the comprehensive operation level of an enterprise, but also an important way to improve the management performance. Nevertheless, the study on this aspect is still lacking. In this paper, we develop a novel method for selecting enterprise's logistics operation mode. First, we give the analysis of main types and characteristics of the logistics operation modes. According to the two dimensions of the Ballou model, i.e., the importance of logistics to enterprise success and the enterprise operation logistics capacity, we set up an evaluation index system for selecting enterprise's logistics operation mode through literature analysis. Then, the each index is evaluated using the fuzzy language assessment method, and evaluation value of each index in the two dimensions is calculated using the 2-tuple fuzzy linguistic representation model. Furthermore, a two-dimensional matrix model for selecting enterprise's logistics operation mode selection is built. According to the model, the right logistics operation mode can be selected. Finally, an example is used to illustrate the practicality and validity of proposed method.